Bioethics Rooted in Justice: Community‐Expert Reflections. (26th April 2022) - Wallace, Gwendolyn
Abstract: Based on interviews that the author and her colleagues conducted with three community organizers, activists, and health care workers—James Manigault‐Bryant, Amika Tendaji, and Amber‐Rose Howard—this essay emphasizes the importance of considering how the field of bioethics might be expanded with the integration of abolitionist perspectives and practices. These individuals were selected as interviewees for this special report on reckoning with anti‐Black racism because of their dedication to Black abolitionist theory and practice and to centering the communities most harmed by state violence. A crucial lesson to be drawn from the conversations held with Manigault‐Bryant, Tendaji, and Howard is that, without centering the experiences of Black health activists and community organizers in bioethics' research, the field is bound to uphold White supremacy, advance colonialism, and neglect entire ways of being in the world.